PENGGUNAAN MODEL UNIFIED OF ACCEPTANCE AND USE TECHNOLOGY (UTAUT) UNTUK MENGANALISA FACTOR DETERMINAN FINTECH DI INDONESIA - Wibowo, Dedi (JURNAL ILMIAH M-PROGRESS, 2021)
This Study aims to contribute to reviewing existing literature of Unified of Acceptance and Use Technology (UTAUT) as an updated model to explain Behavior Intention dan Use Behavior of Technology Acceptance to analyze Determinant Factors for novelty technology of Fintech Industry in Indonesia. The result produced in this study based on analysis of UTAUT model benefit compare to another technology acceptance model, included Technology Acceptance Model, Theory of Reasoned Action and Theory of Planned Behavior. These reviews will share UTAUT Model for future researchers to conceptualize, distinguish and comprehend the underlying technology models and theories that may affect the previous, current and future application of technology acceptance for Fintech adoption in Indonesia.Keywords: UTAUT, Fintech, Behavior Intention, Use Behavior